Glycyrrhizin suppresses the expressions of HMGB1 and ameliorates inflammative effect after acute subarachnoid hemorrhage in rat model. (January 2018) - Ieong, Chengcheng; Sun, Haogen; Wang, Qiangping; Ma, Junpeng
Highlights: Glycyrrhizin suppresses HMGB1 expression after subarachnoid hemorrhage in rats. Glycyrrhizin inhibited BBB permeability after subarachnoid hemorrhage in rats. Glycyrrhizin reduces neuronal degeneration after subarachnoid hemorrhage in rats. Glycyrrhizin reduces neuronal apoptosis after subarachnoid hemorrhage in rats. Glycyrrhizin downregulates IL-1β and TNF-α after subarachnoid hemorrhage in rats. Abstract: High-mobility group box 1 (HMGB1), a nuclear protein that has endogenous cytokine-like activity, is involved in early brain injury after subarachnoid hemorrhage (SAH) by mediating inflammatory response. This study was conducted to investigate the effect of glycyrrhizin as an inhibitor of HMGB1 in a rat SAH model. Experimental SAH was induced by using autologous blood injection to prechiasmatic cistern. 15 mg/kg glycyrrhizin was administered immediately after SAH induction, and then administered once at 6, 12 and 18 h. All the rats were sacrificed at 24 h after neurological assessment and frontal brain tissue was taken for assay. Blood–brain barrier (BBB) permeability was determined by Evans blue (EB) extravasation. The expression of HMGB1 were detected by immunofluorescence, western blot and quantitative real-time PCR. Inflammatory mediators (TNF-α, IL-1β) were measured using specific ELISA. Fluoro-Jade C staining and TUNEL staining was performed for the quantitative assessment of neuronal injury. We found the use of glycyrrhizin significantly improved neurological scores, reduced HMGB1-positive cells, down-regulated mRNA and protein levels of HMGB1, inhibited BBB permeability, and attenuated neuronal cell death and apoptosis after SAH. The up-regulations of inflammation-related molecules (TNF-α, IL-1β) in SAH rats were suppressed by glycyrrhizin treatment. These findings suggest that glycyrrhizin is a potential candidate for the treatment of inflammatory brain injury after SAH.